Glucocorticoid receptor-PPARα axis in fetal mouse liver prepares neonates for milk lipid catabolism - Gianpaolo Rando; Chek Kun Tan; Nourhène Khaled; Alexandra Montagner; Nicolas Leuenberger; Justine Bertrand-Michel; Eeswari Paramalingam; Hervé Guillou; Walter Wahli (eLife, 2016)
In mammals, hepatic lipid catabolism is essential for the newborns to efficiently use milk fat as an energy source. However, it is unclear how this critical trait is acquired and regulated. We demonstrate that under the control of PPARα, the genes required for lipid catabolism are transcribed before birth so that the neonatal liver has a prompt capacity to extract energy from milk upon suckling. The mechanism involves a fetal glucocorticoid receptor (GR)-PPARα axis in which GR directly regulates the transcriptional activation of PPARα by binding to its promoter. Certain PPARα target genes such as Fgf21 remain repressed in the fetal liver and become PPARα responsive after birth following an epigenetic switch triggered by β-hydroxybutyrate-mediated inhibition of HDAC3. This study identifies an endocrine developmental axis in which fetal GR primes the activity of PPARα in anticipation of the sudden shifts in postnatal nutrient source and metabolic demands.